2019
DOI: 10.1038/s41598-019-44261-9
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the NLRC4 inflammasome contributes to poor prognosis in glioma patients

Abstract: Inflammation in tumor microenvironments is implicated in the pathogenesis of tumor development. In particular, inflammasomes, which modulate innate immune functions, are linked to tumor growth and anticancer responses. However, the role of the NLRC4 inflammasome in gliomas remains unclear. Here, we investigated whether the upregulation of the NLRC4 inflammasome is associated with the clinical prognosis of gliomas. We analyzed the protein expression and localization of NLRC4 in glioma tissues from 11 patients b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…These survival plots extend to glioma patients, demonstrating a similar relationship between higher NLRC4 expression and poor prognosis 130 . The study also confirmed increased IL‐1β expression in glioma patients with a poorer outcome, 130 implicating a role of IL‐1β secretion in driving glioma progression. Further studies are therefore required to investigate the tentative link between NLRC4‐mediated IL‐1β secretion and tumor progression, potentially positioning the NLRC4‐IL‐1β pathway as a potential therapeutic target for inhibition in glioma and other cancers.…”
Section: Nlrc4 In Cancermentioning
confidence: 52%
See 1 more Smart Citation
“…These survival plots extend to glioma patients, demonstrating a similar relationship between higher NLRC4 expression and poor prognosis 130 . The study also confirmed increased IL‐1β expression in glioma patients with a poorer outcome, 130 implicating a role of IL‐1β secretion in driving glioma progression. Further studies are therefore required to investigate the tentative link between NLRC4‐mediated IL‐1β secretion and tumor progression, potentially positioning the NLRC4‐IL‐1β pathway as a potential therapeutic target for inhibition in glioma and other cancers.…”
Section: Nlrc4 In Cancermentioning
confidence: 52%
“…Indeed, these mouse studies are supported by data from a cohort of human patients with breast cancer, showing that patients with higher levels of NLRC4 mRNA transcripts have a poorer survival rate 128 . These survival plots extend to glioma patients, demonstrating a similar relationship between higher NLRC4 expression and poor prognosis 130 . The study also confirmed increased IL‐1β expression in glioma patients with a poorer outcome, 130 implicating a role of IL‐1β secretion in driving glioma progression.…”
Section: Nlrc4 In Cancermentioning
confidence: 62%
“…Several evidences indicate that, in glioma, the inflammatory component increases in parallel with tumor aggressiveness and grade ( 48 ). Furthermore, glioma cells are able to recruit glioma associated peripheral monocyte/macrophage and activated microglia (GAMMs) favoring a tumorigenic phenotype ( 49 , 50 ) which plays a central role in drug resistance and treatment failures.…”
Section: Discussionmentioning
confidence: 99%
“…CAPN14 gene is highly expressed in the esophagus and is associated with epithelial barrier impairment observed in esosinophilic esophagitis ( Davis et al, 2016 ). In the NLRC4 inflammasome, upregulation is a marker of poor prognosis in gliomas although the role of inflammasomes in tumors continues to evolve ( Lim et al, 2019 ). The RASGRP3, a RAS activator is known to play a role in several cancers, including breast ( Nagy et al, 2014 ), papillary thyroid ( Qiu et al, 2017 ), and prostate cancers ( Yang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%